(untitled) (Revista UTCiencia: i-ISSN: 1390-6909. e-ISSN: 2602-8263, 2025)
This research focused on determining the relationship between emotional self-regulation in two aspects: cognitive reappraisal and emotional suppression, and the work environment in a company in the automotive sector of Ambato. The study has a quantitative approach, with a non-experimental cross-sectional design and correlational scope. The population consists of 284 employees and was evaluated through two questionnaires: Work Environment Scale (CL-SPC) to measure the level of work background, the Omega reliability ranging from 0.73 to 0.83, indicating an acceptable reliability and Emotional Regulation Questionnaire (ERQ) to assess emotional self-regulation, The questionnaire achieved a content validity between 0.80 and 1.00, indicating high content validity. Pearson correlation yielded a value of (r = 0.156) and a significance of 0.008, indicating a low positive correlation. The main findings include: a) emotional self-regulation has a limited and temporary effect on work environment, it is perceived as a favorable work environment with 49.3%, and b) in the dimensions of workplace, there is a higher number of individuals who employ cognitive reappraisal and emotional suppression in highly favorable and favorable levels. It is concluded that there is a favorable work environment that presents the two emotional regulation strategies (92.1% cognitive reappraisal and 91.4% emotional suppression) as self-regulation mechanisms.